Profile Of Antibiotic Use In ISPA Patients At Bluto Community Health Center, Sumenep Regency, July – December 2024 - Rizqy Nurdiansa; Aldita Cahyani P; Zakiyyah Qurrotul 'Aini (CV. AFDIFAL MAJU BERKAH, 2026)
Acute Respiratory Tract Infections (ARI) are a significant health problem in Indonesia, exacerbated by irrational antibiotic use that triggers antimicrobial resistance (AMR). This study aims to identify patient characteristics and antibiotic use patterns (type, class, dose, duration) in ARI patients at the Bluto Community Health Center, Sumenep Regency, from July to December 2024. Using a retrospective descriptive observational design, purposive sampling resulted in 76 prescriptions from the population of antibiotic prescriptions from doctors for ARI patients (inclusion: treated at the community health center with antibiotics; exclusion: otherwise). Prescription data were analyzed univariately with frequency distribution and percentages using the Slovin formula. The results showed that the majority of patients were male (54%), with peaks in the 0-5 and 46-55 age groups (20% each). Amoxicillin dominated (51%, beta-lactam), followed by cefadroxil (49%, cephalosporin), primarily in the 500 mg tablet and 125 mg/5 ml syrup, with an average duration of 5-7 days. In conclusion, the antibiotic regimen aligns with primary care stewardship guidelines, but monitoring is enhanced to minimize the risk of AMR.